PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU MEDIA AUGMENTED REALITY UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILL KELAS XI PADA METERI SEL DI SMAN 1 ABUNG SELATAN LAMPUNG UTARA - Oktafiani, Raicha; Febriyana, Anggun; Haka, Nukhbatul Bidayati; Kesumawardani, Aryani Dwi (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2025)
Background: Bananas are widely consumed by the people due to their soft texture, easy digested, and can be consumed directly or processed again. This fruit has characteristics that are suitable for Indonesia’s growth climate. Asia ranks first as the largest banana producer, with Indonesia being the third-largest producer. Bananas are generally classified as a source of Vitamin C, also known as Ascorbic Acid. When consuming, many people store it in the refrigerator to keep it fresh. The increase in ascorbic acid content occurrs along with longer storage time. This research aims to study the changes in ascorbic acid levels in bananas due to the effects of storage time at room temperature and refrigerator temperature. Methods: This research use a laboratory experimental by testing the levels of Ascorbic Acid contained in bananas using the spectrophotometry method in April 2024 Results: This research shows that the ascorbic acid content in bananas stored for varying durations at room temperature is lower than refrigerator temperature, and there is an interaction between storage time and storage temperature. Conclusion: The decrease in ascorbic acid levels occurred due to the interaction between storage time and room temperature and refrigerator temperature